Arrhopalites potapovi sp. nov. (Collembola, Symphypleona) from Russia - Vargovitsh, Robert S. (Zootaxa, 2015)
A new springtail species of the family Arrhopalitidae, Arrhopalites potapovi sp. nov., is described. It belongs to the caecus species group characterized by 3,2,1,1,1 anterior setae on dens and separates from Arrhopalites caecus (Tullberg) and other congeners by strongly differentiated cuticular spines on sixth abdominal segment, shape of female subanal appendages and foot complex. It was found under the loose bark of trees from two localities along Lake Baikal and it is the second representative of the genus Arrhopalites Börner sensu stricto in Russia